The Analgesic Effect of Aquoes Extract Ganitri (Elaeocarpus Ganitrus Roxb) Leaves on Mice - Krisdiyanti, Yayu; Miyarso, Chondrosuro; Kiromah, Naelaz Zukhruf Wakhidatul (Prosiding University Research Colloquium, 2021)
Pain is a multidimensional sensory experience caused by tissue damage and is subjective and is a disease that is the main reason for individuals to seek medical help because pain can make it difficult and interfere with activities. Ganitri plant (Elaeocarpus ganitrus Roxb) is a medicinal plant that has benefits in traditional medicine to help cure various diseases, one of which is pain. This study aimed to determine the analgesic activity of aquadest extract of ganitri (Elaeocarpus ganitrus Roxb) leaves against white male mice (Mus musculus) Swiss strain induced by acetic acid. This research is an experimental study with the research subjects in the form of 25 male white mice. The test animals were divided into 5 treatment groups, namely the negative control which was given CMC-Na, the positive control was given mefenamic acid, and the extract group was 100 mg/Kg BW, 200 mg/Kg BW, and 400 mg/Kg BW. The pain inducer given is 1% acetic acid. Observations were made by observing the stretching of the mice which is a pain response that is characterized by stretching in the form of mice pulling their legs back and attaching their stomachs to the bottom of the cage. The stretching of the mice was observed and the percentage of pain protection was calculated. The data that has been obtained was then tested with One Way ANOVA and Post Hoc Games-Howell statistical tests. The results showed that the aquadest extract of ganitri (Elaeocarpus ganitrus) leaves at doses 0f 100, 200, and 400 mg/Kg BW had an analgesic effect on mice and had a significant effect (p<0.05) on mice induced by acetic acid. Ganitri (Elaeocarpus ganitrus) leaf extract dose of 400 mg/Kg BW had the best analgesic effect on mice and was significant with p<0.05.